Inter-turn stator winding fault diagnosis in three-phase induction motors, by Park's vector approach - Cardoso, A. J. Marques (1999)
The subject of on-line detection and location of inter-turn short circuits in the stator windings of three-phase induction motors is discussed, and a noninvasive approach, based on the computer-aided monitoring of the stator current Park's vector, is introduced. Experimental results, obtained by using a special fault producing test rig, demonstrate the effectiveness of the proposed technique, for detecting inter-turn stator winding faults in operating three-phase induction machines. On-site tests conducted in a power generation plant, using the diagnostic instrumentation system developed, are also reported